Employee Proactive Personality in Learning Culture - Nuri Ariani Wulansari; Ita Sulistyo Rini (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2018)
AbstractThe paper attempts to investigate the influences of proactive personality and organizational learning culture on career satisfaction through Leader-Member Exchange quality as a mediating variable. Questionnaire was used as data collection method. The population of this study was Financial Cooperative employees based on health assessment in province level of Semarang City and Regency in 2015. Data was taken from 61 respondents using multi-stage sampling. From the result, it was found that (1) proactive personality influences career satisfaction, (2) organizational learning culture influences career satisfaction, (3) proactive personality influences Leader-Member Exchange quality, (4) organizational learning culture influences Leader-Member Exchange quality, (5) Leader-Member Exchange quality influences career satisfaction, (6) proactive personality influences career satisfaction through Leader-Member Exchange quality as mediator variable, and (7) organizational learning culture influences career satisfaction with Leader-Member Exchange quality as mediator variable. Proactive personality and organizational learning culture influence career satisfaction through Leader-Member Exchange as a mediating variable.